Sulfonic acid-functionalised zeolites for fructose dehydration into 5-hydroxymethylfurfural - Huaizhong Xiang; Yao Zhang; Xin Zhong; Boji Wang; Charalampos Drivas; Mark A Isaacs; Aina Syahida Jamal; Zhipeng Qie; Qiang Zhang; Shaojun Xu; Jesús Esteban; Christopher M A Parlett; et al. (Sustainability Science and Technology)
Biomass-derived 5-hydroxymethylfurfural (HMF) is a versatile and key platform chemical critical to underpinning a sustainable chemical industry based on biomass. This study explores the innovative use of zeolites and hierarchical zeolites, derived through alkaline desilication, as catalytic materials for fructose dehydration. Functionalised with sulfonic acid sites, these materials demonstrate elevated catalytic performance, particularly maximising HMF yields. The increased mesoporosity facilitates higher sulfonic acid incorporation, leading to improved fructose conversion. However, yields are sensitive to reaction duration, with longer time negatively impacting the selectivity towards HMF due to further in-series reactions. Optimal results were achieved under microwave irradiation in a biphasic medium, achieving an HMF selectivity of ∼73% at fructose conversion of ∼88% in just 5 min at 170 °C, emphasising energy efficiency and catalyst accessibility. The best catalyst modifications lead to a reduction in the activation energy of fructose conversion by approximately 35% relative to the uncatalysed process, in conjunction with significant improvements in process sustainability, which align with the United Nations sustainable development goals (SDGs) in Affordable and Clean Energy (SDG 7), Industry, Innovation, and Infrastructure (SDG 9), Responsible Consumption and Production (SDG 12), and Climate Action (SDG 13).